Benefits of Using CD45RA and CD28 to Investigate CD8 Subsets in Kidney Transplant Recipients. Issue 3 (28th January 2016) - Yap, M.; Tilly, G.; Giral, M.; Brouard, S.; Degauque, N.
Abstract : The deleterious role of CD8 T cells in kidney graft outcome has regained interest over the years, and memory T cells are considered as one of the main hurdles to achieve transplantation success. Monitoring the CD8 immune response in transplant recipients involved a heterogeneous combination of markers, but the justification of their choice is rarely stated. Whereas the number of parameters is not an issue in phenotypic analysis, functional assays have to accommodate the cell number with the narrowing of the subset. The aim of the study was to investigate the similarities and differences of the subsets identified using three nomenclatures (CD45RA and CCR7/CD27/CD28) in kidney transplant recipients with stable graft function. We found that all three nomenclatures can identify naïve and effector memory (EM) rheumatoid arthritis T cell CD8 with similar features. Whereas CM CD8 could only be documented using CCR7 and CD45RA, the characteristics of EM CD8 will differ according to the nomenclature. We found that the use of the CD45RA and CD28 gives the benefit of examining two EM populations at early and late differentiation states. This systematic comparison provides a cohesive layout of the advantages of using these nomenclature strategies in kidney transplant recipients to guide the choice of their use. Abstract : The study compares three nomenclatures used to identify CD8 T cell subsets in stable kidney transplant recipients and finds that naïve and terminally differentiated effector memory CD8 cells identified by the different nomenclatures have similar characteristics while central memory and effector memory CD8 cells do not.